ALSUntangled #72: Insulin - Brown, Andrew; Armon, Carmel; Barkhaus, Paul; Beauchamp, Morgan; Bertorini, Tulio; Bromberg, Mark; Cadavid, Javier Mascias; Carter, Gregory T; Crayle, Jesse; Feldman, Eva L; Heiman-Patterson, Terry; Jhooty, Sartaj; et al. (Amyotrophic lateral sclerosis & frontotemporal degeneration, 2024)
ALSUntangled reviews alternative and off-label treatments for people living with amyotrophic lateral sclerosis (PALS). Here we review insulin, which has at least one plausible mechanism for slowing ALS progression. However, pre-clinical studies are limited and there have been no trials in PALS yet. Insulin use in patients without a metabolic need may cause very serious and potentially lethal side effects. While further studies to evaluate potential benefits may be warranted, at this time we cannot endorse insulin treatment to slow ALS progression.
Keywords: Insulin; Amyotrophic Lateral Sclerosis; off-label treatment; lidé; inzulin; insulin; amyotrofická laterální skleróza; Humans; Amyotrophic lateral sclerosis (ALS); metabolism